MUNCULNYA PERUSAHAAN PENERBANGAN BARU DI TENGAH KRISIS EKONOMI - Muhammad Nur Nasution (Universitas Trisakti, 2001)
Even in an economic crisis, Indonesia still establishes at least and new scheduled airlines. This paper discusses the consequences of this phenomena in Indonesia airline industry it is a new agenda for ERA to maintain the health of competition industry.